2019
DOI: 10.1038/s41467-019-09130-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically stable whilst kinetically labile coordination bonds lead to strong and tough self-healing polymers

Abstract: There is often a trade-off between mechanical properties (modulus and toughness) and dynamic self-healing. Here we report the design and synthesis of a polymer containing thermodynamically stable whilst kinetically labile coordination complex to address this conundrum. The Zn-Hbimcp (Hbimcp = 2,6-bis((imino)methyl)-4-chlorophenol) coordination bond used in this work has a relatively large association constant (2.2 × 1011) but also undergoes fast and reversible intra- and inter-molecular ligand exchange process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
187
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(203 citation statements)
references
References 42 publications
2
187
1
Order By: Relevance
“…Besides, a recent report from Bao and coworkers has indicated that the strength and dynamics of metal‐ligand coordination bonds play a critical role in dictating the mechanical properties in PDMS. [ 25 ] Hence, further work is required to optimize the potential of these interactions to obtain functional hydrogel materials. Herein, we have designed hydrogels based on copolymerization of acrylamide and the hydrophobic monomer 6‐(2,2′:6′,2‐′′ Terpyridine‐4′‐yloxy)‐hexylacrylamide ( 1 ) in the presence of metal ions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent report from Bao and coworkers has indicated that the strength and dynamics of metal‐ligand coordination bonds play a critical role in dictating the mechanical properties in PDMS. [ 25 ] Hence, further work is required to optimize the potential of these interactions to obtain functional hydrogel materials. Herein, we have designed hydrogels based on copolymerization of acrylamide and the hydrophobic monomer 6‐(2,2′:6′,2‐′′ Terpyridine‐4′‐yloxy)‐hexylacrylamide ( 1 ) in the presence of metal ions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The research works on dry contact electrodes have been focused on soft conductive polymer composites and intrinsically conductive polymers due to their adaptation to rough and even deformed skin 9,10 . The conductive polymer composites consist of elastomers and conductive nanofillers like metals 11 , nanotubes 12 , nanowires 13 , and nanosheets 14 . The conductive nanofillers are the minority in the elastomer matrix, leading to a small effective contact area between the conductive nanofillers and human skin.…”
mentioning
confidence: 99%
“…. π stacking interactions [31][32][33], ionic interactions [34,35] and metal-ligand interactions [36][37][38][39][40][41][42][43][44], have been incorporated into various kinds of polymers as cross-linkages, leading to repeatable self-healing polymers.…”
Section: Introductionmentioning
confidence: 99%